Pengenalan Wisata Pancer Door Dengan Animasi 3 Dimensi - Hakim, Frestika Cahyo (Fakultas Teknologi Informatika Universitas Surakarta, 2014)
ABSTRACT PancerÂ DoorÂ is a stub at this point in the beach resort city of Pacitan. Therefore, the construction is done by stages. Means of promotion at the time was still using the Figure 2 dimensions, so that the results achieved are less than the maximum. With theÂ 3-D animation is expected that in the future introduction of beach tourism and coastaltourism regional development more detail and clarity. The scope of the problem in this study is how to create multimedia-basedinformation media that can be used as a media introduction to the public beaches. The method used in the manufacture of multimedia-basedinformation is the media, libraryÂ methods, observations, interviews, analysis, productÂ design, testing and implementation. WithÂ theÂ 3-Danimation is expectedÂ to potentially help the media and thepromotion of coastal tourism information. Keyword :Â